Georges Bataille : a critical introduction - Noys, Benjamin, 1969- (Modern European thinkers., 2000)
This is a clear and concise guide to the life and work of the French intellectual Georges Bataille, best known as the author of the celebrated erotic novel, The Story of the Eye. Benjamin Noys introduces Bataille as a writer out of step with the dominant intellectual trends of his day -- surrealism and existentialism -- and shows that it was his very marginality that accounted in large part for his subsequent importance for the post-structuralists and the counterculture, in Europe and in the United States. Treating Bataille's work as a whole rather than focusing, as other studies have done, on aspects of his work (i.e. as social theory or philosophy), Noys' study is intended to be sensitive to the needs of students new to Bataille's work while at the same time drawing on the latest research on Bataille to offer new interpretations of Bataille's œuvre for more experienced readers. This is the first clear, introductory reading of Bataille in English -- challenging current reductive readings, and stressing the range of disciplines affected by Bataille's work, at a time when interest in Bataille is growing. -- Publisher description.